2014
DOI: 10.1007/s11748-014-0493-8
|View full text |Cite
|
Sign up to set email alerts
|

Lobar and sub-lobar lung resection in octogenarians with early stage non-small cell lung cancer: factors affecting surgical outcomes and long-term results

Abstract: In our experience, surgery is a safe and justifiable option for octogenarian patients with early stage NSCLC. Sublobar resection provides an equivalent in-hospital mortality and long-term survival in comparison with open lobectomy but with less postoperative morbidity. Further large-scale randomized studies are necessary to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…Hino et al also reported that octogenarians with postoperative morbidity had significantly poorer prognoses than those without. 12) Our results are consistent with those of Hino et al, suggesting the importance of selecting patients with a low risk of postoperative morbidity.…”
Section: Predictive Factorsupporting
confidence: 93%
See 2 more Smart Citations
“…Hino et al also reported that octogenarians with postoperative morbidity had significantly poorer prognoses than those without. 12) Our results are consistent with those of Hino et al, suggesting the importance of selecting patients with a low risk of postoperative morbidity.…”
Section: Predictive Factorsupporting
confidence: 93%
“…Furthermore, our results are consistent with those of several papers that have demonstrated sub-lobar resection to be associated with reduced surgical risk and better surgical outcomes in elderly patients with lung cancer. 12) On the other hand, recently, Razi et al reported that OS and DFS were significantly lower in the wedge resection group as compared with those in lobectomy, but sublobar resection was not inferior to lobectomy for only T1aN0M0 NSCLC in the elderly and should be considered a viable alternative in this high-risk population. 13) Our study showed that in not only stage I patients (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Notably, while only 1-2% of patients ≥75 years old treated with SABR experience significant morbidity in our study (grade ≥3 toxicity), 45-50% of patients ≥70 years of age experience significant morbidity after surgery (38). Therefore, while surgery can provide excellent outcomes for some elderly patients, even octogenarians (39), many reports show surgery not only has higher morbidity, but also reduced benefit when compared to average-age patients (9), (10), (11), (25), (35), (36), (37). As shown here, however, SABR had similar effectiveness (lung cancer-related survival, PFS) and minimal toxicity in the elderly compared to non-elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited resections like wedges and segmentectomies have recently been reconsidered (32)(33)(34), particularly in the elderly and high-risk population. The previously well documented overall survival benefits of lobectomy over limited resections are not observed in patients older than 75 years (25,(35)(36)(37).…”
Section: General Considerationsmentioning
confidence: 94%